Production of Recombinant Active Human TGFβ1 in Nicotiana benthamiana - Soni, Aditya Prakash; Lee, Juhee; Shin, Kunyoo; Koiwa, Hisashi; Hwang, Inhwan (Frontiers in Plant Science, 2022)
The production of recombinant proteins in plant systems is receiving wider attention. Indeed, various plant-produced pharmaceuticals have been shown to be biologically active. However, the production of human growth factors and cytokines in heterologous systems is still challenging because they often act as complex forms, such as homo- or hetero-dimers, and their production is tightly regulated in vivo. In this study, we demonstrated that the mature form of human TGFβ1 produced and purified from Nicotiana benthamiana shows biological activity in animal cells. To produce the mature form of TGFβ1, various recombinant genes containing the mature form of TGFβ1 were generated and produced in N. benthamiana. Of these, a recombinant construct, BiP:M:CBM3:LAP[C33S]:EK:TGFβ1, was expressed at a high level in N. benthamiana. Recombinant proteins were one-step purified using CBM3 as an affinity tag and microcrystalline cellulose (MCC) beads as a matrix. The TGFβ1 recombinant protein bound on MCC beads was proteolytically processed with enterokinase to separate mature TGFβ1. The mature TGFβ1 still associated with LAP[C33S] that had been immobilized on MCC beads was released by HCl treatment. Purified TGFβ1 activated TGFβ1-mediated signaling in the A549 cell line, thereby inducing phosphorylation of SMAD-2, the expression of ZEB-2 and SNAIL1, and the formation of a filopodia-like structure. Based on these results, we propose that active mature TGFβ1, one of the most challenging growth factors to produce in heterologous systems, can be produced from plants at a high degree of purity via a few steps.